Prediction of Surface Flow by Forcing of Climate Forecast System Reanalysis Data - Jajarmizadeh M.; Sidek L.M.; Mirzai M.; Alaghmand S.; Harun S.; Majid M.R. (Springer Netherlands, 2023)
Arid regions; Calibration; Forecasting; Hydrology; Meteorology; Rain; Runoff; Uncertainty analysis; Calibration and validations; CFSR; Hydrological simulations; Meteorological variables; Reanalysis; Sequential uncertainty fittings; Soil and water assessment tool; SWAT model; Data visualization